A higher probability of subsequent stroke and ischemic heart disease in migraine patients: a longitudinal follow-up study in Korea - Mi Jung Kwon; Hyo Geun Choi; Yoo Hwan Kim; Joo-Hee Kim; Hyun Taek Rim; Heui Seung Lee; Jae Keun Oh; In Bok Chang; Joon Ho Song; Ji Hee Kim (The Journal of Headache and Pain, 2023)
Abstract Background Whether migraine is related to the risk of cardiovascular diseases (CVDs) remains unclear. Therefore, we conducted a longitudinal follow-up study to address the association between migraine and the development of CVDs in Korea. Methods Using data from the national health screening cohort, we included 45,246 patients diagnosed with migraine between 2002 and 2019 and age-, sex-, income-, and residential region-matched nonmigraine participants at a ratio of 1:4. Participants with previous CVDs were excluded. Cox proportional hazards regression models were used to estimate the hazard ratios of three CVDs, stroke, ischemic heart disease, and heart failure, in patients with migraine after adjusting for potential cardiovascular risk factors. Results The incidence rate differences of stroke, ischemic heart disease, and heart failure among patients with migraine were 2.61, 1.69, and 0.11, respectively. The probability of developing stroke and ischemic heart disease in patients with migraine was significantly higher than that in controls after controlling for multiple confounders (adjusted hazard ratio [HR] = 1.35, 95% confidence interval [CI] = 1.31–1.39 and adjusted HR = 1.31, 95% CI = 1.26–1.35, respectively). However, when compared with the patients without migraine, patients with migraine did not have an increased HR of developing heart failure (adjusted HR = 1.01, 95% CI = 0.95–1.08). The overall migraine group, as well as groups stratified by migraine subtypes with and without aura, each showed a significantly higher probability of subsequent stroke and ischemic heart disease than the control group. Conclusions Our longitudinal follow-up study demonstrated a significant association between the presence of migraine and the development of stroke and ischemic heart disease in Korea, even after adjusting for cardiovascular risk factors.